PHYLOGENETIC ORIGIN OF FIVE ALGERIAN SHEEP BREEDS - niema ghernouti; Daniel Petit; Semir Bechir Suheil Gaouar (Journal of Experimental and Molecular Biology, 2022)
In order to perform a phylogeny study of five Algerian sheep breeds, a sample of 26 animals belonging to Algerian sheep breeds was analysed. Multiple alignment of mitochondrial sequences was performed after the introduction of other highly similar mitochondrial sequences from different regions of the world. 20 different haplotypes were observed, with a nucleotide diversity of 0.60863 and a haplotype diversity of 0.932. The evolutionary history deduced from the study of genetic distances, and phylogeny based on the maximum likelihood model, showed that these five local breeds belong to the mixture of the two world haplogroups (A and B).